Web-based application for used textbook catalogue with content-based title recommender / Muhammad Rifqi Hafiz Rafisam - Hafiz Rafisam, Muhammad Rifqi (2017)
The textbook is a book used as a standard source of information in order to gain knowledge regarding a specific content. Nowadays, college textbooks are becoming increasingly expensive and recently has become an issue to college students. Based on the survey conducted at Faculty of Computer and Mathematical Science (FSKM) students in Universiti Teknologi Mara (UiTM), Jasin Campus, it has been concluded that students find it difficult to buy textbooks for the courses they are enrolled with. Furthermore, respondents stated that the cost of textbooks are expensive and are becoming a burden and it also become the factor for discouraging them from purchasing textbooks for their classes. Therefore, this application is developed to help students recommend used textbooks based on the student’s course and semester. Besides that, students can search and find textbooks more easily using the recommendation system. This web based system is developed based on Rapid Application Development (RAD) methodology, which consists of four stages which are the planning phase, design phase, development phase and the cutover phase. The requirement gatherings was conducted and the system was developed and designed. Content-based filtering technique is used and implemented in order to recommend the used textbooks based on course and semester by filtering the results to the users. Finally, functionality testing was conducted to confirm that all features work as intended and the system is feasible to be used.